Cytotoxic Effect of Girinimbine on HepG2 Cells - Mohan, Suvita Syam (2011)
Girinimbine, a naturally occurring carbazole alkaloid, has been shown to possess wide range of pharmacological effects. However, to date, there is no literature evidencing the anticancer effect of this compound in human hepatocellular carcinoma (HCC). Here, we report that in vitro treatment of HepG2 cells (HCC cell line) with girinimbine inhibited cell proliferation and induced cell death in a dose-dependent and time-dependent manner which were analyzed by MTT and LDH assay (IC50 61 ± 2.3 μM, 56 ± 3.6 μM, and 40 ± 2.7 μM for 24, 48 and 72 h respectively). Girinimbine induced HepG2 cell death was identified by morphological features of apoptosis with the aid of Hoechst 33342 dye. The DNA analysis of girinimbine treated HepG2 cells with agarose electrophoresis resulted in significant DNA fragmentation with an increase in time dependent manner. There was 0.4 units (OD) (p<0.05) time-dependent increase in caspase-3 activity. Further, girinimbine also induced accumulation of cells in G0/G1 phase (approximately 7.5 % (p<0.05) compared to control cells) in the HepG2 cell cycle progression. The intracellular level of reactive oxygen species (ROS) in HepG2 cells increased time-dependently after girinimbine treatment. The initial level of ROS in HepG2 cells was 105.20 ± 5.26 % which reached 132.70 ± 6.63 % (p<0.05) after 3 h. The intracellular antioxidant, GSH level after an initial elevation to 30 % to that of control decreased to 20 % after girinimbine treatment at 3 h. Mitochondrial damage, also increased from by girinimbine treatment as observed by the loss of mitochondrial membrane potential in flow cytometric analysis. The loss of mitochondrial membrane potential for control cells was 4.30 ± 0.21 %, while after girinimbine treatment the mitochondrial membrane potential became 25.30 ± 1.26 % at 3 h. The comet assay revealed a significant (P<0.05) 5-fold increase than the control upon exposure to 100 μM girinimbine after 3 h incubation. Girinimbine also induces Hsp 70 and Hsp 90 expression in a dose-dependent manner up to concentration of 100 μM and time -dependent manner after 24 h incubation. However, pretreatment of antioxidants ascorbic acid and catalase showed decrease in ROS level, Hsp level and mitochondrial damage, oxidative DNA damage, but an increase in GSH level. All these events are happening at an early stage (i.e., at 3 h after girinimbine treatment itself), suggesting the oxidative stress mechanism in inducing apoptosis in HepG2 cells. Taken together, these results strongly support the hypothesis that, after exposure, girinimbine suppressed the growth of HepG2 cells via induction of G0/G1 phase arrest and oxidative stress mediated apoptosis driven by mitochondrial pathway.